Environmental data (Stable Isotopes and channel measurements) from the Cass River, Tekapo, New Zealand - Holly Harris (17661015) (2025)
Data collection including Metadata and RCode. Collection includes data from a field survey of the Cass River braidplain resources, and predator feeding pathways. This collection includes physical instream measurements and stable isotopes dC13 and d15N for invertebrates, fish, lizards, and bird species across the river braidplain. Please read the Metadata for full data details and description of each file. Study co-ordinates and area description: -43.872812, 170.464226; -43.880391, 170.510661; -43.871111, 170.483838; -43.882216, 170.488988 Lower Cass River |Te Awa-a-Takamira, from Godley peaks bridge to river delta, including southern and northern spring and tributary systems within LINZ land (bounded by southern and northern private properties)